Effects of water volume rates on spray deposition and control of tarnished plant bug [Hemiptera : Miridae] in strawberry crops - Panneton, B.; Bélanger, A.; Vincent, C.; Piché, M.; Khelifi, M. (Phytoprotection, 2000)
Field experiments were performed on the effect of three volumes of application on spray deposition and insecticidal efficacy against the tarnished plant bug (Lygus lineolaris) in two strawberry (Fragaria ananassa) cultivars, Kent and Chambly. The rate of application of malathion was kept constant at 4.5 kg a.i. ha-1 for volumes of application of 500 and 1500 L ha-1. Plant coverage was measured using a fluorescent tracer applied at volumes of application of 500, 1000 and 1500 L ha-1. The tracer was recovered from samples taken from different plant locations and on the ground. Tarnished plant bug populations were evaluated 24 hours before and after insecticidal treatment. When coverage data were normalized for a fixed active ingredient rate, an increase in the volume of application from 500 to 1500 L ha-1 frequently had no effect on the amount of tracer recovered at the various locations. On some occasions, an increase in volume of application resulted in a decrease in the amount of tracer recovered, i.e. leaves at the top and bottom of the canopy (Kent), sepals (Kent). Tarnished plant bug population control was commercially acceptable at 500 and 1500 L ha-1.